Menelusuri Jejak Spiritualisme melalui Kajian Feminisme Sastra dalam Cerpen "Umi Kalsum" Karya Djamil Suherman - Uun Widayanti; Ahmad Ilzamul Hikam (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This article explores the dimensions of spiritualism and existential feminism in the short story Umi Kalsum by Djamil Suherman using a qualitative descriptive approach combined. The study focuses on interpreting symbolic and ideological elements within the text that reflect the search for life’s meaning, spiritual awareness, and the position of women within a patriarchal social structure. Data were obtained through literature review and analyzed in depth through the processes of data reduction, presentation, and interpretive reflection, with validity ensured through source triangulation and repeated readings. The findings reveal that the character Umi Kalsum represents a devout woman who lives under strict social norms, yet possesses strong spiritual and inner resilience. Spiritual values are reflected in her submissive and sincere acceptance of suffering, while existential feminism is expressed through her inner conflict and struggle for personal freedom. The protagonist’s tragic end serves as a symbolic protest against the restrictive social order imposed on women. This short story illustrates how spiritual experience and existential awareness can act as liberating forces in the face of gender-based injustice.